Bangladesh, national culture, and heritage : an introductory reader - Ahmed, A. F. Salahuddin, 1924-2014.; Chowdhury, Bazlul Mobin (Dhaka : Distributor, Pathak Shamabesh, 2004)
Contributed articles on history and civilization of Bangladesh in 19th and 20th century.
Includes bibliographical references and index.
Keywords: Bangladesh -- History -- 19th century; Bangladesh -- History -- 20th century; Bangladesh -- Civilization -- 19th century; Bangladesh -- Civilization -- 20th century